Modelagem hidrodinâmica e do transporte de sedimentos da Baía de Vitória, ES : impacto do aprofundamento do canal estuarino do Porto de Vitória - Lacerda, Kaio Calmon (2016)
he deepening of an estuary navigation channel, even if in the order of meters, can result in different impacts on the patterns of water level, currents and salinity gradient. And this commonly results in modifications of erosion and deposition patterns and suspended sediment concentration (SSC). Therefore,itcan cause undesirable effects such as greater flood risk and creation of a new and/or larger maintenance dredging requirement. A dredging project of Vitória Port channel, located in Vitória Bay estuary, has been started in 2012 with the goal of reaching ~14 m of depth, when the channel had 10.6 to 13 m depths. And thus allow berthing of large ships. Potential impacts of the deepening of Vitória Port channel are investigated using the hydrodynamic and sediment transport Delft3D model forced by tide, wind, atmospheric pressure and thermohaline gradients. The numerical model successfully reproduced the observed water level, current, temperature, salinity andSSC at the Vitória Bay. The results suggests that the deepening of the channel results in a larger impact in a localized way, leading to the decrease of the flow velocity, CSS and erosion and deposition values, over deepened region. There was a mean reduction of 20% in the velocity magnitude and for water level the results suggest poor impact of millimeters. For SSC the results sugest a reduction of about 30% (8 mg/L). The erosion/deposition patterns were most affected in the region between the Vitória BayMouth and Vitória Port, with differences of 20-60% of the results obtained upon deepening. The reduction of the bed shear stress over the deepened region, and thus of the sediment flux from the bed, was the main factor responsible for the decrease obtained in the SSC and erosion/deposition results.Therefore the results suggest that the deepening of Vitória Port channel may decrease flow velocity in the deepened region, with a consequent reduction of erosion rates in this portion of Vitória Bay.